PENGARUH BRAND IMAGE DAN HARGA TERHADAP KEPUASAN PEMBELI DAN PENGARUHNYA TERHADAP LOYALITAS - Agus Santoso; Hartini Hartini (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
This study aims to examine whether there is an effect of brand image and price on buyer satisfaction and its impact on buyer loyalty of Instant Noodle Products by Overseas Students at the Sumbawa University of Technology. This type of research is quantitative with the population is the Sumbawa people who consume instant noodles. The data collection technique is using a questionnaire using google form and the sampling technique is purposive sampling with a total of 100 respondents. The results show that Brand Image has a significant effect on consumer satisfaction of Instant Noodle Products by overseas students at the Sumbawa University of Technology. Price has a significant effect on consumer satisfaction of instant noodle products by overseas students at the Sumbawa University of Technology. Satisfaction has a significant effect on consumer loyalty to instant noodles by overseas students at the Sumbawa University of Technology. Brand Image through consumer satisfaction has a significant effect on consumer loyalty for instant noodle products by overseas students at the Sumbawa University of Technology and prices through consumer satisfaction have a significant effect on consumer loyalty for instant noodle products by overseas students at the Sumbawa University of Technology